Building Public Awareness of Development Communicators, Educators and Evaluation - Scheunpflug, Annette (OECD Publishing, 2008)
The Millennium Development Goals, the aid effectiveness agenda, and global interdependence have contributed to more demand and a sense of urgency for greater public awareness and learning about these promises, and challenges, in OECD countries. Donors and practitioners could make greater use of evaluations, and their findings, to increase the effectiveness and results of public communication, advocacy and education about global development. The first step is to understand the evaluation process and respect its rigours. The second is to acknowledge and learn how to deal with the political nature of evaluation, the third is to understand its limitations. DAC members, along with their partners, should work together to strengthen evaluation of public awareness and learning by creating a space (e.g. website) to share perspectives, experiences and results from evaluation; pooling resources for scientific research on the long-term impact of public awareness raising activities; building a stronger knowledge base for what works and what doesn't work in this sector; and finally, working together to develop minimum standards for the evaluation of communication, advocacy and education about global development
Keywords: Development